A budget allocation analysis and poverty alleviation strategy in Aceh post conflict and tsunami - Agussabti Agussabti; Jeliteng Pribadi; T Zulham; Sofyan Sofyan (Proceedings of AICS - Social Sciences, 2017)
This paper analyses budget allocation and poverty alleviation strategy in Aceh’s post conflict and tsunami. It is aimed (1) to identify conditions and the cause of poverty in Aceh, (2) to analyze poverty alleviation budget and programs in Aceh and (3) to find a suitable poverty alleviation strategy in post conflict and tsunami in Aceh. The study was conducted in 2015-2016 using budget data of 2013 and 2014 collected from 7 districts in Aceh, 3 districts representing the west coast, 3 other representing the east coast, and 1 in the capital city of Banda Aceh. Meanwhile, the survey was conducted through in-depth interview technique reinforced by FGD in six districts i.e. Bener Meriah, Gayo Lues, Pidie Jaya, North Aceh, Aceh Barat, and Simeulue. The results show that Aceh’s poverty budget allocation is irrelevance and inconsistent. This is allegedly due to the limited capacity and commitment of decision makers to poverty alleviation. Poverty in Aceh is caused by natural, structural and cultural problems. The budget allocations for poverty alleviation programs are not well managed and unstructured and thus tend to be less effective in reducing poverty in Aceh. It is recommended that poverty alleviation strategies in Aceh should optimize the development of rural sectors such as agriculture, livestock, fisheries, poultry, dairy, and handicrafts, by stimulating the involvement and coordination of wider stakeholders.